2020
DOI: 10.3899/jrheum.200863
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Clinical Risk Factors for Incident Rheumatoid Arthritis-associated Interstitial Lung Disease

Abstract: Objective To determine the association between novel lifestyle factors on risk of rheumatoid arthritis-associated interstitial lung disease (RA-ILD), define the threshold at which smoking increases RA-ILD risk, and calculate the degree to which known lifestyle and clinical factors predict RA-ILD. Methods This nested case-control study matched incident RA-ILD cases to RA non-ILD controls on age, sex, RA duration, rheumatoid factor, and time from exposure assessment to RA-ILD. Exposures included education, body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 48 publications
1
57
2
Order By: Relevance
“…The results of degenerative macular diseases were different from the MR study of CRP on age-related macular degeneration (AMD) that highlighted higher circulating CRP levels leading to increases in risk for all forms of AMD (38). An observational study showed that baseline CRP levels predicted long-term interstitial lung disease progression, and another found that high-positive CRP was associated with rheumatoid arthritisassociated interstitial lung disease, which also conflicts with our causal evidence (39,40). The observational evidence for the effect of CRP on metatarsalgia, idiopathic pulmonary fibrosis, and disorders of the skin remains lacking.…”
Section: Identified Associations In the Finngen Populationcontrasting
confidence: 65%
“…The results of degenerative macular diseases were different from the MR study of CRP on age-related macular degeneration (AMD) that highlighted higher circulating CRP levels leading to increases in risk for all forms of AMD (38). An observational study showed that baseline CRP levels predicted long-term interstitial lung disease progression, and another found that high-positive CRP was associated with rheumatoid arthritisassociated interstitial lung disease, which also conflicts with our causal evidence (39,40). The observational evidence for the effect of CRP on metatarsalgia, idiopathic pulmonary fibrosis, and disorders of the skin remains lacking.…”
Section: Identified Associations In the Finngen Populationcontrasting
confidence: 65%
“…We were unable to account for some important risk factors, such as smoking and disease activity, and did not consider other common or rare genetic risk factors,14 17 all of which are likely to further contribute to the risk. We did not have information about histological or radiological patterns of ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also identified RA-specific characteristics, such as RA-related autoantibodies and articular disease activity, as risk factors for RA-ILD. [11][12][13][14] Thus, there may be a synergistic relationship between the MUC5B promoter variant and RA for RA-ILD risk. Other established RA-ILD risk factors include older age at RA onset, male sex, cigarette smoking and longer RA duration, among others.…”
Section: Towards Clinical Significance Of the Muc5b Promoter Variant And Risk Of Rheumatoid Arthritis-associated Interstitial Lung Diseasmentioning
confidence: 99%
“…However, the prevalence of UIP is generally reported to be higher than would be expected by chance alone, considering the independent prevalence of IPF and RA. Previous studies have also identified RA-specific characteristics, such as RA-related autoantibodies and articular disease activity, as risk factors for RA-ILD 11–14. Thus, there may be a synergistic relationship between the MUC5B promoter variant and RA for RA-ILD risk.…”
mentioning
confidence: 97%